Unravelling the Relationship between Governance Indicators and Foreign Direct Investment in Tanzania: An Empirical Analysis - Raphael, Gwahula (PAN-AFRICAN JOURNAL OF BUSINESS MANAGEMENT, 2023)
Foreign Direct investment (FDI) is recognized as a significant source of capital inflows that can stimulate economic growth in developing countries. In order to attract and benefit from FDI, governments have implemented various economic reforms and focused on improving governance indicators. This study investigated the causality effect of governance indicators on FDI inflows in Tanzania. The governance indicators examined in this study include; rule of law, regulatory quality, government effectiveness, control of corruption, voice and Accountability, political stability and absence of violence. Before measuring the causality effect between the variables, a stationarity, test was conducted using the Augmented Dickey-Fuller (ADF) test. Then the Granger Causality Test was used to address two-way linkages between variables. The data used in the study was secondary quantitative time series data obtained from the World Bank Worldwide Governance Indicators and the Bank of Tanzania from 1996 to 2021. The findings suggested a long-run causality running from governance indicators to FDI inflows in Tanzania. In the short run, voice and accountability, political stability and absence of violence, government effectiveness, regulatory quality, rule of law, and control of corruption individually influence FDI inflows. Furthermore, the Granger causality test indicates that voice and accountability and political stability and absence of violence Granger cause FDI inflows. The other governance indicators also exhibited significant causality with FDI inflows. These results call for policy makers in Tanzania to focus on strengthening governance framework, ensure accountability, enhance investor protection, ensure political stability, promote the rule of law and prevent corruption in achieving increased FDI for sustained economic growth.